Genotoxic potential of selected medicinal plant extracts in human whole blood cultures - Karina Harutyunyan; Karine Balayan; Gohar Tadevosyan; Manush Hayrapetyan; Ruzanna Musayelyan; Ruzanna Grigoryan; Lusine Khondkaryan; Natalya Sarkisyan; Nelly Babayan (Shahrekord University of Medical Sciences, 2019)
Introduction: Many plant-derived products despite wide usage are not scientifically evaluated for their safety and efﬁcacy. Therefore, in the present study, we aimed to evaluate the cytotoxic and genotoxic activities of Polygonum aviculare L., Equisetum arvense L., Plantago lanceolata L. and Artemisia absinthium L. ethanolic extracts in human white blood cells. Methods: Cell viability was assayed by trypan blue exclusion method, while the genotoxicity was tested by cytokinesis-block micronucleus (CBMN) assay upon cells stimulation with noncytotoxic concentrations of the plant extracts. Results: None of the plant extracts showed high cytotoxic activity. At the same time, only extract of P. lanceolata did not present any mutagenic activity, while E. arvense, P. aviculare and A. absinthium were clearly genotoxic. Conclusion: Caution is advice in the case of long-term use of E. arvense, P. aviculare and A. absinthium herbal medicines by population.